Shape controlled synthesis of nanostructured magnesium oxide particles in supercritical carbon dioxide with ethanol cosolvent - Kim, Sang Woo; Kim, Kwang Deok; Moon, Dong Ju (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Magnesium compound nanoarchitectures with controlled shape were prepared through carbonation reaction of magnesium hydroxide and carbon dioxide in supercritical carbon dioxide-ethanol mixtures and their formation mechanism were discussed. The leaf-like brucite and the floral-like hydromagnesite nanosheets with a monoclinic structure were formed at the reaction temperature of less than 80 degrees C and 100 degrees C, respectively. The floral architecture started to transform the nanosheets with stacked arrangements at the elevated temperature above 130 degrees C, and compeletely transformed to cube-like magnesite with a trigonal crystal structure at 150 degrees C in progress of the carbonation reaction of hydromagnesite and carbon dioxide in a supercritical CO2 with ethanol cosolvent. The morphologies of the product architectures were artificially controlled by the phase transition driven morphological changes. With further increasing temperature to 600 degrees C, the micro-meso porous magnesium oxide architectures with high surface area were finally formed by decarbonation of the magnesite cubes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: MINERAL CARBONATION; MGO; NANOPARTICLES; CATALYSTS; SEQUESTRATION; STABILITY; MG(OH)(2)